A Population-Based Analysis of the Risk of Glomerular Disease Relapse after COVID-19 Vaccination. Issue 12 (December 2022) - Canney, Mark; Atiquzzaman, Mohammad; Cunningham, Amanda M.; Zheng, Yuyan; Er, Lee; Hawken, Steven; Zhao, Yinshan; Barbour, Sean J.
Significance Statement: Several reports have described glomerular disease relapse after coronavirus disease 2019 (COVID-19) vaccination, but without proper controls, determining whether this association is real or due to chance is not possible. In this population-level cohort of 1105 adult patients with stable glomerular disease, a first dose of a COVID-19 vaccine was not associated with relapse risk; however, receiving a subsequent vaccine dose was associated with a two-fold higher risk of relapse. The increase in absolute risk associated with vaccination was low (1%–5%), and the majority of affected patients did not require a change in immunosuppression or biopsy. These results represent the first accurate assessment of the relative and absolute risks of glomerular disease flare associated with COVID-19 vaccination and underscore the favorable risk-benefit profile of vaccination in patients with glomerular disease. Visual Abstract: Abstract : Background: Although case reports have described relapses of glomerular disease after COVID-19 vaccination, evidence of a true association is lacking. In this population-level analysis, we sought to determine relative and absolute risks of glomerular disease relapse after COVID-19 vaccination. Methods: In this retrospective population-level cohort study, we used a centralized clinical and pathology registry (2000–2020) to identify 1105 adult patients in British Columbia, Canada, with biopsy-proven glomerular disease that was stable on December 14, 2020 (when COVID-19 vaccines first became available). The primary outcome was disease relapse, on the basis of changes in kidney function, proteinuria, or both. Vaccination was modeled as a 30-day time-varying exposure in extended Cox regression models, stratified on disease type. Results: During 281 days of follow-up, 134 (12.1%) patients experienced a relapse. Although a first vaccine dose was not associated with relapse risk (hazard ratio [HR]=0.67; 95% confidence interval [95% CI], 0.33 to 1.36), exposure to a second or third dose was associated with a two-fold risk of relapse (HR=2.23; 95% CI, 1.06 to 4.71). The pattern of relative risk was similar across glomerular diseases. The absolute increase in 30-day relapse risk associated with a second or third vaccine dose varied from 1%–2% in ANCA-related glomerulonephritis, minimal change disease, membranous nephropathy, or FSGS to 3%–5% in IgA nephropathy or lupus nephritis. Among 24 patients experiencing a vaccine-associated relapse, 4 (17%) had a change in immunosuppression, and none required a biopsy. Conclusions: In a population-level cohort of patients with glomerular disease, a second or third dose of COVID-19 vaccine was associated with higher relative risk but low absolute increased risk of relapse.